Immune response and protective efficacy of an experimentally developed inactivated oil adjuvant Brucella abortus vaccine in BALB/c mice (Journal of Advanced Veterinary and Animal Research, 2024)
Objectives: This study evaluated the immunogenicity and protective efficacy of an inactivated oil adjuvant B. abortus vaccine in BALB/c mice. Materials and Methods: Mice in group A (n = 30) received subcutaneous (s.c.) immunization with 0.1 ml of vaccine (1.5 × 107 inactivated B. abortus biovar 3 per mouse) and were boosted 4 weeks later. Group B (n = 30) received normal saline as unvaccinated controls. BALB/c, vaccinated and unvaccinated mice were challenged with B. abortus biovar 3 (3 × 107 cells per mouse) at 6 weeks post-vaccination (WPV). Serum antibody levels were assessed at 0, 1, 2, 3, 4, 5, and 6 WPV using RBPT and i-ELISA. Cellular-mediated immune (CMI) response was evaluated by measuring the skin thickness of vaccinated mice’s left and right hind footpads sensitized with B. abortus soluble antigen and PBS, respectively. Bacterial persistence and spleen histopathological lesions were evaluated at 1, 2, and 3 weeks post-challenge. Results: The vaccinated mice developed B. abortus-specific serum IgG response from 2 WPV. The highest serum IgG titer was observed in 5-6 WPV (p < 0.001). The skin thickness was significantly higher in the left footpad than the right footpad (p < 0.001). Huge cellular infiltration with mononuclear and polynuclear cells was noticed in the dermis and sub-dermis areas of the left footpad. The spleen weight and bacterial load in the spleen were significantly reduced in vaccinated mice compared to unvaccinated control mice (p < 0.001). Conclusions: The inactivated oil adjuvant B. abortus vaccine induced both humoral and CMI responses, which conferred protection in BALB/c mice against virulent challenge infections.J. Adv. Vet. Anim. Res., 11(4): 914-923, December 2024http://doi.org/10.5455/javar.2024.k841